(untitled) (Medicine Today, 2019)
Introduction: Achalasia is a benign idiopathic disorder caused by progressive neuronal degeneration in the mesenteric plexus of Auerbach, which causing non-relaxing, hypertensive lower esophageal sphincter (LES) and aperistalsis of the esophageal body. This functional damage is irreversible and the treatment of esophageal achalasia is mainly palliative. Case Report: Our patient is a 55 years old lady presents with progressive dysphagia, regurgitation, chest pain and weight loss. After clinical examination and relevant investigations, she was diagnosed as a case of achalasia of cardia of oesophagus. Discussion: She was prepared for Heller’s myotomy with antireflux procedure. Operative procedure was done under general anaesthesia. Conclusion: Postoperative recovery was good. The patient is asymptomatic, general condition improved and found healthy on follow up after one year. Medicine Today 2019 Vol.31(2): 128-130